2017
DOI: 10.11648/j.ajlm.20170204.15
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Trypanocidal Activity of <i>Bidens pilosa</i> and <i>Physalis peruviana</i> Against <i>Trypanosoma brucei rhodesiense</i>

Abstract: Abstract:Trypanosomiasis is a protozoan disease that causes death and morbidity to man, and also severely limits livestock productivity in endemic areas. It is caused by different species of trypanosomes that occur in Africa, South America and Asia. Although chemotherapy is the main method of trypanosomiasis control, the few drugs in the market are faced with challenges of drug resistance, high toxicity and very costly. There is also no likelihood of a vaccine to control new outbreaks and there are no new drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…In both strains of T. cruzi , the inhibition percentages at various concentrations for each fraction and the crude extract did not differ significantly. This finding reaffirms the concentrations’ dose-response effect, as previously demonstrated for B. pilosa extracts, which displayed significant antiprotozoal activity against Leishmania amazonensis [ 4 ], antimalarial activity [ 28 ], and anti- T. brucei rhodesiense in a dose-dependent manner [ 5 ]. Various studies have reported these concentration ranges, often falling between 500 μg/ml and over 1,000 μg/ml against various microorganisms.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In both strains of T. cruzi , the inhibition percentages at various concentrations for each fraction and the crude extract did not differ significantly. This finding reaffirms the concentrations’ dose-response effect, as previously demonstrated for B. pilosa extracts, which displayed significant antiprotozoal activity against Leishmania amazonensis [ 4 ], antimalarial activity [ 28 ], and anti- T. brucei rhodesiense in a dose-dependent manner [ 5 ]. Various studies have reported these concentration ranges, often falling between 500 μg/ml and over 1,000 μg/ml against various microorganisms.…”
Section: Discussionsupporting
confidence: 85%
“…Subsequently, a 25 g sample was pulverized to a fine powder using a mortar. This powder was subjected to extraction in a Soxhlet apparatus using 500 ml of absolute methanol (TEDIA, Fairfield, OH, USA), with indirect heating facilitated by a magnetic stirrer set at 60 V (C-MAG HS 10, Carl Roth, Karlsruhe, Germany) for 48 h [ 3 , 5 ]. The methanolic extract was then filtered using Whatman filter paper No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation